Self-inflicted skin lesions: the importance of a proper diagnostic and therapeutic approach - Dimitrov, Dimitre; Reszke, Radomir; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Patients with self-inflicted skin lesions (SISL) are most often referred to dermatologists. Since psychological and psychiatric conditions might be the underlying reasons for the behavior of these patients, the psychology-associated component should always be kept in mind when approaching such individuals. Objective. To discuss distinctive aspects of the approach towards patients with SISL and emphasize the most relevant issues concerning the management of psychodermatoses. Case report. We present a case of a 13-year-old girl with a 6-month history of skin lesions misdiagnosed as allergic contact dermatitis. Conscientious history taking and physical examination enabled the diagnosis of SISL. Conclusions. The proper approach to patients presenting with psychodermatoses differs from that for other dermatological patients and requires considering several additional aspects. We would like to emphasize the distinguishing aspects and importance of the proper approach to patients with SISL that might aid clinicians in diagnosing and treating these individuals in the future.